Mixed mode partitioning of beam-like geometries: A damage dependent solution. (November 2015) - Conroy, M.; Kinloch, A.J.; Williams, J.G.; Ivankovic, A.
Highlights: Fracture is modelled in beam-like geometries using cohesive zone models. The global mode partition is studied as a function of cohesive properties. The mode partition varies from local to global solution as zone length increases. The normalised mode mix is uniquely dependent on the normalised zone length. A semi-analytical partitioning analysis is proposed and is shown to perform well. Abstract: The current work studies the fracture mode partition in beam-like geometries as a function of cohesive properties. It is observed that the mode mixity exhibits a unique dependence on the cohesive zone length scale, where the lower and upper bounds are given by the local and global partitioning. Based on this observed unique dependency, a new semi-analytical cohesive analysis (SACA) is proposed for partitioning. This partitioning method is applied to previously conflicting experimental data in the literature, and physically consistent results are obtained in each case, suggesting that this novel SACA method can be used to obtain accurate mixed mode partitioning values.